The Metallicities of Low Stellar Mass Galaxies and the Scatter in the Mass-Metallicity Relation - Zahid, H. Jabran (2012)
In this investigation, we quantify the metallicities of low-mass galaxies by constructing the most comprehensive census to date. We use galaxies from the Sloan Digital Sky Survey (SDSS) and DEEP2 survey and estimate metallicities from their optical emission lines. We also use two smaller samples from the literature that have metallicities determined by the direct method using the temperature sensitive [O III]λ4363 line. We examine the scatter in the local mass-metallicity (MZ) relation determined from 20,000 star-forming galaxies in the SDSS and show that it is larger at lower stellar masses, consistent with the theoretical scatter in the MZ relation determined from hydrodynamical simulations. We determine a lower limit for the scatter in metallicities of galaxies down to stellar masses of 107 M ⊙ which is only slightly smaller than the expected scatter inferred from the SDSS MZ relation and significantly larger than what has been previously established in the literature. The average metallicity of star-forming galaxies increases with stellar mass. By examining the scatter in the SDSS MZ relation, we show that this is mostly due to the lowest metallicity galaxies. The population of low-mass, metal-rich galaxies have properties that are consistent with previously identified galaxies that may be transitional objects between gas-rich dwarf irregulars and gas-poor dwarf spheroidals and ellipticals.